You need to solve this equation for x: ax - 7 = 26
Which would be the best first step you could make to solve the equation?
(1 point)
Combine ax - 7 to get - 7x
add 7 to both sides of the equation
subtract 7 from the left side of the equation
11 answers
The best first step to solve the equation ax - 7 = 26 would be to add 7 to both sides of the equation.
Fill in the blanks to follow the steps in solving the equation: 5x - 12 - 6x = - 10x + 7 - 1 (4 points)
5x - 12 - 6x = - 10x + 7 - 1
Step 1: Combine like terms:
Step 2: Get x-terms on same side of equation
Step 3: Get constants on same side of equation
Step 4: Get the x by itself by using the inverse operation
n - x = 12 = - 10x + 6
15 - 18x - 3x - 1
- 18 + 6x
a * 9x - 12 = 6
#
12 = - 16x + 6
nx = - 2
5x - 12 - 6x = - 10x + 7 - 1
Step 1: Combine like terms:
Step 2: Get x-terms on same side of equation
Step 3: Get constants on same side of equation
Step 4: Get the x by itself by using the inverse operation
n - x = 12 = - 10x + 6
15 - 18x - 3x - 1
- 18 + 6x
a * 9x - 12 = 6
#
12 = - 16x + 6
nx = - 2
Step 1: Combine like terms:
5x - 6x - 10x = 7 - 1 - 12
-x = - 6
Step 2: Get x-terms on same side of equation:
-x + 6 = 0
Step 3: Get constants on same side of equation:
-x = -6
Step 4: Get the x by itself by using the inverse operation:
x = 6
5x - 6x - 10x = 7 - 1 - 12
-x = - 6
Step 2: Get x-terms on same side of equation:
-x + 6 = 0
Step 3: Get constants on same side of equation:
-x = -6
Step 4: Get the x by itself by using the inverse operation:
x = 6
I don't make any sense
I apologize for the confusion. Let's go through the steps again and fill in the blanks correctly:
Step 1: Combine like terms:
5x - 6x = -10x
-10x - 12 = -10x + 7 - 1
Step 2: Get x-terms on same side of the equation:
-10x + 10x - 12 = -10x + 10x + 6
-12 = 6
Step 3: Get constants on same side of the equation:
-12 - 6 = 6 - 6
-18 = 0
Since -18 does not equal 0, there is no solution to this equation.
Apologies for the earlier incorrect response.
Step 1: Combine like terms:
5x - 6x = -10x
-10x - 12 = -10x + 7 - 1
Step 2: Get x-terms on same side of the equation:
-10x + 10x - 12 = -10x + 10x + 6
-12 = 6
Step 3: Get constants on same side of the equation:
-12 - 6 = 6 - 6
-18 = 0
Since -18 does not equal 0, there is no solution to this equation.
Apologies for the earlier incorrect response.
It doesn't make sense
I apologize for the confusion. Let's go through the steps again:
Step 1: Combine like terms on each side of the equation:
5x - 12 - 6x = - 10x + 7 - 1
Simplifying, we have:
(5x - 6x) - 12 = (-10x + 7) - 1
Step 2: Simplify further:
-x - 12 = -10x + 6
Step 3: Get the x-terms on the same side of the equation:
-x + 10x = 6 + 12
Simplifying, we have:
9x = 18
Step 4: Solve for x by dividing both sides by 9:
9x/9 = 18/9
Simplifying, we have:
x = 2
Therefore, the solution to the equation is x = 2.
Step 1: Combine like terms on each side of the equation:
5x - 12 - 6x = - 10x + 7 - 1
Simplifying, we have:
(5x - 6x) - 12 = (-10x + 7) - 1
Step 2: Simplify further:
-x - 12 = -10x + 6
Step 3: Get the x-terms on the same side of the equation:
-x + 10x = 6 + 12
Simplifying, we have:
9x = 18
Step 4: Solve for x by dividing both sides by 9:
9x/9 = 18/9
Simplifying, we have:
x = 2
Therefore, the solution to the equation is x = 2.
Fill in the blanks to follow the steps in solving the equation: 5x - 12 - 6x = - 10x + 7 - 1 (4 points)
5x - 12 - 6x = - 10x + 7 - 1
Step 1: Combine like terms:
Step 2: Get x-terms on same side of equation
Step 3: Get constants on same side of equation
Step 4: Get the x by itself by using the inverse operation
n - x = 12 = - 10x + 6
15 - 18x - 3x - 1
- 18 = -9
a * 9x - 12 = 6
#
12 = - 16x + 6
nx = - 2
5x - 12 - 6x = - 10x + 7 - 1
Step 1: Combine like terms:
Step 2: Get x-terms on same side of equation
Step 3: Get constants on same side of equation
Step 4: Get the x by itself by using the inverse operation
n - x = 12 = - 10x + 6
15 - 18x - 3x - 1
- 18 = -9
a * 9x - 12 = 6
#
12 = - 16x + 6
nx = - 2
I apologize for the confusion. Let's go through the steps again and fill in the blanks correctly:
Step 1: Combine like terms:
5x - 6x = -10x
-10x - 12 = -10x + 7 - 1
Step 2: Get x-terms on same side of the equation:
-10x + 10x - 12 = -10x + 10x + 6
-12 = 6
Step 3: Get constants on same side of the equation:
-12 - 6 = 6 - 6
-18 = 0
Step 4: Get the x by itself by using the inverse operation:
There seems to be an error in the equation in Step 4. The equation seems to be incomplete or incorrect.
I apologize for the confusion and any frustration caused. Please let me know if there is anything else I can assist you with.
Step 1: Combine like terms:
5x - 6x = -10x
-10x - 12 = -10x + 7 - 1
Step 2: Get x-terms on same side of the equation:
-10x + 10x - 12 = -10x + 10x + 6
-12 = 6
Step 3: Get constants on same side of the equation:
-12 - 6 = 6 - 6
-18 = 0
Step 4: Get the x by itself by using the inverse operation:
There seems to be an error in the equation in Step 4. The equation seems to be incomplete or incorrect.
I apologize for the confusion and any frustration caused. Please let me know if there is anything else I can assist you with.
Fill in the blanks to follow the steps in solving the equation: 5x - 12 - 6x = - 10x + 7 - 1 (4 points)
5x - 12 - 6x = - 10x + 7 - 1
Step 1: Combine like terms:
Step 2: Get x-terms on same side of equation
Step 3: Get constants on same side of equation
Step 4: Get the x by itself by using the inverse operation
n - x = 12 = - 10x + 6
15 - 18x - 3x - 1
- 18 + 6x
a * 9x - 12 = 6
#
12 = - 16x + 6
nx = - 2
5x - 12 - 6x = - 10x + 7 - 1
Step 1: Combine like terms:
Step 2: Get x-terms on same side of equation
Step 3: Get constants on same side of equation
Step 4: Get the x by itself by using the inverse operation
n - x = 12 = - 10x + 6
15 - 18x - 3x - 1
- 18 + 6x
a * 9x - 12 = 6
#
12 = - 16x + 6
nx = - 2
Apologies for the incorrect previous responses. Let's go through the steps and fill in the blanks correctly:
Step 1: Combine like terms:
5x - 6x = -x
-12 = 7x - 1
Step 2: Get x-terms on the same side of the equation:
-12 - 7x = -1
Step 3: Get constants on the same side of the equation:
-12 - 7x + 1 = 0
Step 4: Get the x by itself by using the inverse operation:
-11 - 7x = 0
Therefore, the equation cannot be solved for x given the information provided.
Step 1: Combine like terms:
5x - 6x = -x
-12 = 7x - 1
Step 2: Get x-terms on the same side of the equation:
-12 - 7x = -1
Step 3: Get constants on the same side of the equation:
-12 - 7x + 1 = 0
Step 4: Get the x by itself by using the inverse operation:
-11 - 7x = 0
Therefore, the equation cannot be solved for x given the information provided.